2005
DOI: 10.1021/jp0546507
|View full text |Cite
|
Sign up to set email alerts
|

NOx Formation in the Plasma Treatment of Halomethanes

Abstract: A nonthermal, atmospheric pressure plasma, made-up of a BaTiO3 packed-bed reactor, has been used to study the formation of NOx and N2O during the plasma destruction of a range of volatile organic compounds (VOCs) and hazardous air pollutants, including chlorinated, brominated, fluorinated, and iodinated methane species, in a carrier gas of air. Using the plasma destruction of pure air as a baseline, it is found that the amount of NOx formed is unaffected by the addition of a few hundred parts per million of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…In a plasma discharge in air, NO, NO 2 and N 2 O are commonly produced [17,24] and are undesirable endproducts. They arise because excited-state nitrogen atoms formed in the plasma discharge react with molecular oxygen to form NO, which is further oxidised by atomic oxygen and ozone to NO 2…”
Section: Discussionmentioning
confidence: 99%
“…In a plasma discharge in air, NO, NO 2 and N 2 O are commonly produced [17,24] and are undesirable endproducts. They arise because excited-state nitrogen atoms formed in the plasma discharge react with molecular oxygen to form NO, which is further oxidised by atomic oxygen and ozone to NO 2…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study [29] showed that, the spectrum of the N 2 RGA was dominated by the radiative species such as N 2 (C), N 2 (B), and N 2 + (B). Nevertheless, the radiative lifetimes of these species are very short in atmospheric pressure plasmas [50,51], thus significantly limiting their contribution to the chemical reactivity of the N 2 plasma. Therefore, these species were not considered in this model, which is commonly seen in other modeling studies of CH 4 /N 2 plasmas [41,46,50].…”
Section: Excited Nitrogen Speciesmentioning
confidence: 99%
“…[17,55,58] Al ater study conductedb yT ang et al [59] also investigated plasma-based NO x synthesis using metal-oxide catalysts, which was worth comparing with Patil et al [55] because both studies examined the plasma-based NO x synthesis for as pecific energy inputr ange between 1300 and 1800 JL À1 .R esults from Patil [59] These two studies also investigated the effect of the plasma-discharge parameters, the results of which provided understanding of the potential plasma influence on the characterization of catalyst surfaces. [61] Note that BaTiO 3 was mainly used as the dielectric to generate plasma. [57,59] Another aspect of the synergyb etween catalyst and plasma is the influence of plasma on the catalyst.…”
Section: Plasma-catalyst Interactionsmentioning
confidence: 99%
“…In as tudy by Harling et al BaTiO 3 wasu sed to facilitate plasma-assisted NO x production. [61] Note that BaTiO 3 was mainly used as the dielectric to generate plasma. However, its catalytic activity should also be taken into account based on previousevidences of plasmacatalysti nteractions.…”
Section: Plasma-catalyst Interactionsmentioning
confidence: 99%